Pengelolaan Sumber Daya Manusia Untuk Meningkatkan Kerjasama Tim - Hanifah Nur Aqilah; Rosita Pratiwi Junaidi; Mochammad Ishaq; Iriani Ismail (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The purpose of this study is to find out how to manage human resources to improve teamwork at PT. Firdaus Kurnia Indah located in Bangkalan Regency. The research method used is qualitative research using two data, namely primary and secondary. Primary data obtained through observation and direct interviews. While our secondary data can be from a collection of literature. The results of our research show that the existence of good teamwork in a company can make cooperation that occurs within the company also run smoothly so as to avoid conflicts between other employees and superiors..